SIRKUMSISI PEREMPUAN SEBUAH TRADISI KUNO YANG EKSIS DAN TERLARANG (STUDI KASUS MESIR) - Pamungkas, Jati (Asketik : Jurnal Agama dan Perubahan Sosial, 2020)
This study discuss about women circumcision. This study took a sample of women circumcision that occurred in Egypt because women circumcision tradition is done massively in their community. This study also discuss about women circumcision from socio-cultural perspective such as the beliefs in good things from the tradition. This study also discuss about the controversies of women circumcision tradition that World Health Organization (WHO) considers very dangerous for women. The purpose of this study is to explain that women circumcision tradition is an ancient tradition that existed thousands years ago even before Islam. Women circumcision potentially very dangerous and beliefs about good things of it that are believed by community actually are not always realized in social facts.